Disposable ultrasound-sensing chronic cranial window by soft nanoimprinting lithography - Hao Li (Nature Portfolio, 2019)
Chronic cranial windows (CCW) enable long-term imaging of brain activity, but usually they only provide passive optical access to the tissue. Here the authors develop an active CCW integrated with an ultrasound detector which enables long-term photoacoustic imaging of the cortical vasculature in live mice with higher image quality.